TOO-LOW MAGNETIC INCLINATIONS IN CENTRAL ASIA: AN INDICATION OF A LONG-TERM TERTIARY NON-DIPOLE FIELD? - Si J.; Van der Voo R. (My University, 2001)
Observed Tertiary palaeolatitudes in central Asia are more southerly (by about 1600 km on average) than those predicted from the Eurasian reference palaeopoles. Subsequent northward displacements of the central Asian terranes are unlikely to have been this large. In this study we analyse to what extent non-dipole fields, especially octupole fields, can explain this phenomenon. A global (zonal) octupole field manifests itself in two ways. (1) Because the reference APWP is based mostly on results from the UK and North America, its palaeopoles will be far-sided as seen from the North Atlantic, but near-sided as seen from eastern Asia, giving predicted palaeolatitudes that are too high. (2) An octupole field contribution produces observed palaeolatitudes, as calculated with the dipole formula for central Asia, that are too low. Both effects therefore increase the palaeolatitude anomalies in Asia. We find that an octupole/dipole field ratio (G3) of 0.06 or greater will reduce the palaeolatitude discrepancies significantly and is of the same magnitude as the G3 estimate of a recent analysis of Early Tertiary European and North American data.